The T4/T3 quotient as a risk factor for differentiated thyroid cancer: a case control study - Mark Sasson; Emily Kay-Rivest; Rami Shoukrun; Anca Florea; Michael Hier; Veronique-Isabelle Forest; Michael Tamilia; Richard J. Payne (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background The incidence of thyroid nodules is increasing among patients in North America. Few of these nodules harbour malignancy, thus further research is required to identify predictive markers of malignant thyroid disease. This study set out to understand the relationship between the levels of fT4 and fT3 and differentiated thyroid cancer. Methods A case-control study was conducted with 142 cases and 86 controls from the McGill University Teaching Hospitals. All patients underwent thyroid surgery. Cases were defined as patients with malignant nodules confirmed on final pathology and controls were defined as patients with benign nodules. The serological levels of TSH, fT4 and fT3 were measured preoperatively. Odds ratios were determined for each parameter and logistic regressions were calculated between markers and probability of malignancy. Additionally, fT4 values were divided by fT3 values (fT4/fT3 quotient) for each patient and an odds ratio was calculated. Results Amongst cases, the mean TSH was 2.25 ± 0.360U/mL, fT4 was 14.8 ± 0.689pmol/L, and fT3 was 4.65 ± 0.463pmol/L. Amongst controls, the mean TSH was 2.36 ± 1.68U/mL, fT4 was 14.3 ± 1.71pmol/L, and fT3 was 5.27 ± 0.957pmol/L. Patients in the control group were more likely to have low TSH, while patients in the case group would have high fT4 and patients in the control group were more likely to have a low fT4. The OR for patients with TSH >4.4U/mL was 2.13 (0.97, 4.65), and for patients with TSH <0.4U/mL was 0.46 (0.22, 0.95). The OR for patients with fT4 > 16pmol/L was 2.10 (1.09, 4.06), and for patients with fT4 < 10pmol/L was 0.45 (0.20, 0.98). The OR for patients with fT3 > 5.5pmol/L was 0.39 (0.14, 1.28). The OR for patients with fT3 < 3pmol/L was 1.83 (0.25, 13.69). The average fT4/fT3 was 3.39 ± 0.206 for cases and 2.93 ± 0.467 for controls. The fT4/fT3 quotient was considered high if it was >3.3 (OR =6.00 (2.94, 12.25)). Conclusion In this study, a direct relationship between high levels of fT4 and malignancy was uncovered. Furthermore, low levels of TSH and fT4 increased the likelihood that a nodule was benign. In this study a fT4/fT3 ratio >3.3 increased the risk of malignancy by 3.6 times (p-value =0.0013).